Cytotoxic T cells in HIV2 seropositive Gambians. Identification of a virus-specific MHC-restricted peptide epitope. - Gotch, F; McAdam, SN; Allsopp, C; Gallimore, A; Elvin, J; Kieny, M; Hill, A; Mcmichael, A; Whittle, H (1993)
A preliminary study of gag-specific, MHC-restricted CD8+ CTL has been performed in nine Gambian patients infected with HIV2. Such CTL were present in at least 55% of patients in fresh peripheral blood mononuclear cells without the requirement for in vitro restimulation. We have identified a nonamer peptide from HIV2 gag that is recognized by CD8+ HLA-B53 CTL using an amino acid sequence motif predicted from analysis of endogenous peptides eluted from HLA-B53 molecules. This peptide, from an HIV2/SIV conserved sequence, has previously been reported to be recognized by CTL from non-human primates vaccinated with recombinant vaccinia virus expressing the gag protein of SIV or infected with SIV virus. HLA-B53-restricted, HIV2 gag-specific CTL did not recognize target cells expressing HIV1 gag proteins, indicating that no cellular cross protection to HIV1 could be expected in this case.